Effect of self-administered interventions on raising awareness of suicidal behavior and crystal meth use in adolescents from Aguascalientes, México - Kalina Isela Martínez Martínez; Marielena Eudave Patiño; Yancarlo Lizandro Ojeda Aguilar; Lorenia Robles Villarreal (INFAD)
Self-administered interventions for adolescents, which can be delivered through digital platforms using comics, present an opportunity for preventing suicidal behavior and methamphetamine use in the state of Aguascalientes. This state ranks fourth nationally in suicides among individuals aged 15 to 29 (INEGI, 2022) and has a higher percentage of people who have used methamphetamines at least once in their lifetime compared to the national average (EBCO, 2018). The goal was to evaluate the effectiveness of an intervention to increase awareness of suicidal behavior and crystal meth use, as well as to assess students’ perceptions of the intervention. 567 adolescents participated in the intervention for preventing suicidal behavior, and 604 in the intervention for crystal meth use. Data were collected through tests administered before and after presenting a comic, in addition to evaluating the intervention itself. Due to differences in the availability of equipment at the institutions, some students completed the intervention and evaluation on a digital platform, while others used paper questionnaires.  The results show that the average number of correct responses on the post- test was higher than on the pretest for both the suicidal behavior and crystal meth use interventions. Both differences were statistically significant (p<.001 in both cases), and the evaluation of the intervention indicates that students perceive the platform and comics as potentially useful for preventing crystal meth use and suicidal behavior among adolescents. The intervention showed promising results in raising awareness about suicidal behavior and crystal meth use among adolescents in Aguascalientes. Future research should explore its applicability in other regions as well as consider evaluating its long-term effects.